Towards intercultural communication congruence in Sino-African organisational contexts - Chigwendere, Fungai Beaula (Rhodes University, Faculty of Commerce, Department of Management, 2018)
Despite the prevalence of theories and research that could serve as guidelines for addressing intercultural communication challenges such as misunderstanding, ineffectiveness and inappropriateness in communication in Sino-African organisational contexts, the continued existence of these challenges suggests the inadequacy of such theories. Accordingly, in consideration of African and Chinese cultural perspectives, the aim of this study was to develop a hybrid intercultural communication congruence (HICC) framework in order to enhance intercultural communication and achieve intercultural communication congruence in Sino-African organisational contexts. In this study, intercultural communication congruence means effectiveness and appropriateness in intercultural communication. To achieve the study aim, an interpretive pragmatism paradigm was adopted, comprising a two-pronged approach of a synthesis of extant literature and theory as well as an empirical qualitative study, both underpinned by cross-cultural management theory. Based on the synthesis of literature and theory, a generic theoretical intercultural communication congruence framework underpinned by intercultural communication awareness - a state where communicants understand communication orientation and manner of communication in their own and their counterparts' culture - was developed. A further contribution was a theoretical contextualisation of the generic theoretical intercultural communication congruence framework, resulting in a theoretical framework for intercultural communication awareness in Western, African and Chinese cultures and a theoretical intercultural communication congruence framework specific to Sino-African organisational contexts. Thereafter, with the aim of validating the intercultural communication awareness dimension of the theoretical intercultural communication congruence framework specific to Sino-African organisational contexts, an empirical study was conducted with a sample of seven African and eight Chinese experts using indepth interviews with open-ended and semi-structured questions. Based on qualitative content analysis, six intercultural communication awareness enablers or conditions that enable people to understand communication in different cultures and contexts for the purposes of attaining intercultural communication awareness emerged. These were cultural orientation, manner of communication, orientation to rules and protocol, individual dispositions, intercultural communication influences and intercultural communication variations. An integration of the intercultural communication awareness enablers into the generic theoretical intercultural communication congruence framework results in an updated generic theoretical intercultural communication congruence framework. Then, informed by the updated generic theoretical intercultural communication congruence framework, a further contribution of this study was an empirical verification of the intercultural communication awareness dimension of the theoretical intercultural communication congruence framework specific to Sino-African organisational contexts to result in a final hybrid intercultural communication congruence framework for Sino-African organisational contexts supported by the perspectives of those involved in interaction, rather than predetermined standards of other cultures. Empirical findings suggest that both African and Chinese colleagues maintain a sense of collectivism in the Sino- African organisational context, although this is demonstrated differently. In addition, African colleagues display a blended manner of communication characterised by a mix of Western and African ways while the Chinese manner is contextual and governed by roles and relationships. In African culture, rules and protocol are negotiated, aimed at social maintenance, while strong cultural patriotism ensures strict adherence in Chinese culture. In respect of individual dispositions, African people are seen as open and accommodating while the Chinese disposition could be described as closed and ambiguous. Also evident in the findings is the existence of within-culture differences and influence of noncultural factors on intercultural communication that should be addressed in order to achieve intercultural communication congruence. Finally, the frameworks developed and the methodological processes followed will stimulate academic debate and raise numerous questions for future research. Immediate future research could be geared towards refining the concepts of intercultural communication awareness, intercultural communication congruence and the hybrid intercultural communication congruence framework for Sino-African organisational contexts. At a management practice level, intercultural communication awareness insights provide a reference point for intercultural communication enhancement strategies and interventions in Sino-African organisational contexts.
Keywords: Intercultural communication -- Africa; China -- Foreign economic relations -- Africa; Communication in organizations -- Cross-cultural studies; Corporate culture -- Cross-cultural studies; Africa -- Relations -- China; China -- Relations -- Africa